Assessment risk of osteoporosis in Chinese people: relationship among body mass index, serum lipid profiles, blood glucose, and bone mineral density - Cui RT (Dove Medical Press, 2016)
Rongtao Cui,1 Lin Zhou,2 Zuohong Li,2 Qing Li,2 Zhiming Qi,2 Junyong Zhang3 1Department of Orthopedic and Trauma Surgery, Surgical Research, Duisburg-Essen University Hospital, Essen, Germany; 2Department of Orthopedics, Dalian Central Hospital, Dalian, 3Department of Gastroenterology, Shandong Provincial Hospital, Jinan, People’s Republic of China Objective: The aim of our study was to investigate the relationship among age, sex, body mass index (BMI), serum lipid profiles, blood glucose (BG), and bone mineral density (BMD), making an assessment of the risk of osteoporosis.Materials and methods: A total of 1,035 male and 3,953 female healthy volunteers (aged 41–95 years) were recruited by an open invitation. The basic information, including age, sex, height, weight, waistline, hipline, menstrual cycle, and medical history, were collected by a questionnaire survey and physical examination. Serum lipid profiles, BG, postprandial blood glucose, and glycosylated hemoglobin were obtained after 12 hours fasting. BMD in lumbar spine was measured by dual-energy X-ray absorptiometry scanning.Results: The age-adjusted BMD in females was significantly lower than in males. With aging, greater differences of BMD distribution exist in elderly females than in males (P<0.001), and the fastigium of bone mass loss was in the age range from 51 to 55 in females and from 61 to 65 years in males. After adjustment for sex, there were significant differences in BMD among BMI-stratified groups in both males and females. The subjects with a BMI of <18.5 had a higher incidence of osteoporosis than BMI ≥18.5 in both sexes. BMD in type 2 diabetes mellitus with a BG of >7.0 mmol/L was lower than in people with BG of ≤7.0 mmol/L (P<0.001). People with serum high-density lipoprotein cholesterol levels of ≥1.56 mmol/L had a greater prevalence of osteoporosis compared with high-density lipoprotein cholesterol ≤1.55 mmol/L. Logistic regression with odds ratios showed that no association was found among total cholesterol, triglyceride, low-density lipoprotein cholesterol, glycosylated hemoglobin, postprandial blood glucose and BMD.Conclusion: The present study further confirmed that factors such as age, sex, weight, BMI, high-density lipoprotein cholesterol, and diabetes are significant predictors of osteoporosis in the Chinese people. Keywords: risk assessment, BMI, blood glucose, serum lipid profiles, osteoporosis